Knowledge-based system for business-ICT alignment - Kania, Krzysztof (Oparty na wiedzy system dopasowania biznes-IT, 2011)
One of the approaches to solve the problem of business-ICT alignment is a heuristic approach. It involves the use of external sources of knowledge and teams of experts.On the basis of a thorough diagnosis of the business needs and knowledge about available ICT products, they recommend appropriate solutions. But it is relatively expensive solution that requires access to the group of experts. As an alternative approach we propose using the knowledge stored in models of business goals and processes and a rule-based expert system for reasoning about matching specific ICT with them. The article describes a framework using knowledge base based on maturity models that allows the realization of this task as well as supporting improvement of business processes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 68-80
Keywords: business-ITC alignment